Thyroidectomy for the treatment of Graves’ thyrotoxicosis in thioamide-induced agranulocytosis and sepsis - Colin L Knight; Shamil D Cooray; Jaideep Kulkarni; Michael Borschmann; Mark Kotowicz (Endocrinology, Diabetes & Metabolism Case Reports, 2017)
A 51 year old man presented with sepsis in the setting of thioamide-induced agranulocytosis. Empiric broad-spectrum antibiotics was followed by directed narrow-spectrum antibiotics, and his neutrophil count recovered with support from granulocyte-colony stimulating factor (G-CSF) analogue transfusions. After a brief period of multi-modal therapy for nine days including potassium iodide (Lugol’s iodine), cholestyramine, propanolol and lithium to temper his persisting hyperthyroidism, a total thyroidectomy was performed while thyroid hormone levels remained at thyrotoxic levels. Postoperative recovery was uncomplicated and he was discharged home on thyroxine. There is limited available evidence to guide treatment in this unique cohort of patients who require prompt management to avert impending clinical deterioration. This case report summarises the successful emergent control of thyrotoxicosis in the setting of thioamide-induced agranulocytosis complicated by sepsis, and demonstrates the safe use of multi-modal pharmacological therapies in preparation for total thyroidectomy.